Multimodal fiber‐probe spectroscopy allows detecting epileptogenic focal cortical dysplasia in children. Issue 6 (9th January 2017) - Anand, Suresh; Cicchi, Riccardo; Giordano, Flavio; Conti, Valerio; Buccoliero, Anna Maria; Guerrini, Renzo; Pavone, Francesco Saverio
Abstract : We evaluated the diagnostic capability of a multimodal spectroscopic approach for classifying normal brain tissue and epileptogenic focal cortical dysplasia in children. We employed fluorescence spectroscopy at two excitation wavelengths (378 nm and 445 nm) and Raman spectroscopy (at 785 nm excitation) for acquiring fluorescence and Raman spectra from 10 normal brains, 16 focal cortical dysplasia specimens and 1 cortical tuber tissue sites using a custom‐built multimodal optical point spectroscopic system. We used principal component analysis combined with leave‐one‐sample‐out‐cross‐validation for tissue classification. The study resulted in 100% sensitivity and 90% specificity using the information obtained from fluorescence at two distinct wavelengths and Raman spectroscopy for discriminating normal brain tissue and focal cortical dysplasia. Our results demonstrate that this methodology has the potential to be applied clinically for the detection of focal cortical dysplasia and can help to improve as precise as possible surgical resection of the dysplastic tissue during surgery for epilepsy.Schematic draw of the experimental setup used for fiber‐probe spectroscopy. Abstract : Here we investigate the application of fluorescence spectroscopy (at 378 nm and 445 nm excitation) and Raman spectroscopy (at 785 nm excitation) to discriminate normal brain tissue and focal cortical dysplasia. Multimodal spectroscopic approach yielded 100% sensitivity and 90% specificity by exploiting the information obtained from different spectroscopic techniques. Our results demonstrate the application of multimodal spectroscopic approach for the possible surgical resection of the dysplastic tissue during surgery for epilepsy.